2018
DOI: 10.1186/s13063-018-2493-y
|View full text |Cite|
|
Sign up to set email alerts
|

Survey indicated that core outcome set development is increasingly including patients, being conducted internationally and using Delphi surveys

Abstract: BackgroundThere are numerous challenges in including patients in a core outcome set (COS) study, these can vary depending on the patient group. This study describes current efforts to include patients in the development of COS, with the aim of identifying areas for further improvement and study.MethodsUsing the COMET database, corresponding authors of COS projects registered or published from 1 January 2013 to 2 February 2017 were invited via a personalised email to participate in a short online survey. The su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 19 publications
0
46
0
Order By: Relevance
“…Heterogeneity in methodology and specifically in reported outcomes in randomized trials prohibits the use of data in systematic reviews and meta‐analyses, thus preventing firm conclusions and consensus in the clinical application of the research evidence. Variation in outcome measures renders this task even more challenging …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heterogeneity in methodology and specifically in reported outcomes in randomized trials prohibits the use of data in systematic reviews and meta‐analyses, thus preventing firm conclusions and consensus in the clinical application of the research evidence. Variation in outcome measures renders this task even more challenging …”
Section: Introductionmentioning
confidence: 99%
“…Variation in outcome measures renders this task even more challenging. 6,7 We aimed to identify and classify all the reported outcomes and outcome measures in randomized controlled trials on apical prolapse interventions. We used the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guideline to report the search and selection of studies.…”
Section: Introductionmentioning
confidence: 99%
“…This is reflective of COSs in general and is not a methodological problem specific to cancer. Recent research has shown an improvement in patient participation in more recently published COSs [6,11]. Although thirteen studies did include patients in COS development, there is still great variability in the level of participation of patients in COS development.…”
Section: Discussionmentioning
confidence: 99%
“…however, the most appropriate way to facilitate inclusion remains largely unknown [2,7]. Participation in Delphi surveys is the most popular method used for patient inclusion by COS developers, but mixed methods techniques are becoming increasingly popular [7,8]. COS developers using mixed method techniques often conduct patient interviews as an adjunct to a systematic review of the literature to identify an initial list of potential outcomes for inclusion in a Delphi consensus survey [9].…”
mentioning
confidence: 99%